2015
DOI: 10.1039/c5ra09883a
|View full text |Cite
|
Sign up to set email alerts
|

The first study of surface modified silica nanoparticles in pressure-decreasing application

Abstract: In this study, hydrophobic silica nanoparticles were prepared by the surface modification of silica nanoparticles using dimethyldichlorosilane. Fourier transform infrared spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy were employed for the characterization of the raw silica nanoparticles and modified silica nanoparticles. The results showed that methyl groups are successfully grafted on the surface of silica nanoparticles. The titration method was employed to quantitatively dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The EOR application of NPs is also hampered by poor dispersibility or stability in the injection fluid (e.g., water). Nanoparticles have an immense surface free energy triggered by their ultra-small size and large surface area, which increases the tendency of the NPs to aggregate/agglomerate in solution in an attempt to gain the low energy state [23]. As the NPs approach each other, their surface functionalities at the fluid–rock interfaces are reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EOR application of NPs is also hampered by poor dispersibility or stability in the injection fluid (e.g., water). Nanoparticles have an immense surface free energy triggered by their ultra-small size and large surface area, which increases the tendency of the NPs to aggregate/agglomerate in solution in an attempt to gain the low energy state [23]. As the NPs approach each other, their surface functionalities at the fluid–rock interfaces are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the EOR mechanisms to the reduced oil and water IFT and the formation of wedge film between the oil and the rock surface that readily altered the wettability. The effect of surface-modified silica NPs to decrease the water injection pressure for EOR purposes was studied by Dai et al [23] and Zhao et al [28]. The authors observed that, during the injection of nanofluid, NPs adsorbed and formed layers on the rock surface, thereby crowding the water out on it and increasing the water flowing channels, thus decreasing the injection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polymer/surfactant coating on the surface of the NPs was found to promote nanofluid properties which include mobility, foams, emulsion, stability, and solubility of the fluids in a porous media [59,61,63,64]. Some experiments have shown that coating silicon dioxide nanoparticles with surfactant/polymer has revealed a productive outcome for EOR [59,61,[65][66][67]. Furthermore, coating silica NP with Al 2 O 3 NP has made them appear with a higher surface area, which resulted in better recovery than with bare silica or alumina, as reported by Negin et al [34].…”
Section: Influence Of Nps' Surface Modification For Nanofluids Stabilitymentioning
confidence: 99%
“…Functional nanoparticles have been applied in aspects such as wettability, surfactivity, pressure decrease, and augmented injection because of the unique properties of nanoscale particles. Sharma et al (2014), Dai et al (2015), Zhang H. et al (2016), Emrani and Nasr-El-Din (2017), and Li et al (2019). In addition, the modification of the surfaces of SiO 2 nanoparticles with pH-responsive, light-responsive, and CO 2 /N 2 -responsive groups has also been reported increasingly Jiang W. et al, 2016;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 97%